(untitled) (Acta Scientiarum. Technology, 2014)
Differences in the levels of antinutritional components - Kunitz trypsin inhibitor and phytic acid - were determined for conventional and genetically modified soybean cultivated in Londrina and Ponta Grossa, South Brazil. Trypsin inhibitor levels in the conventional cultivars of Londrina and Ponta Grossa varied from 14.56 mg g-1 (BRS 267) to 20.40 mg g-1 (BRS 261) and from 13.51 mg g-1 (BRS 232) to 19.65 mg g-1 (BRS 268), respectively, whereas in the genetically modified (GM) cultivars, they were found to be 14.16 mg g-1 (BRS 242 RR) to 18.21 mg g-1 (BRS 255 RR) for Londrina, and 13.68 mg g-1 (BRS 244 RR) to 18.73 mg g-1 (BRS 256 RR) for Ponta Grossa. Average levels of phytic acid in the Londrina´s conventional and GM samples were estimated as 2.05 and 1.78 mg g-1, respectively, and in the Ponta Grossa conventional and GM samples, the respective average values were lower, 1.60 and 1.51 mg g-1. Â